Photocatalytic activity of MgFe2O4:TiO2 composite for degrading methylene blue - Hasniah Aliah; Elis Sabilil Hidayah; Ryan Nur Iman; Asti Sawitri; Andhy Setiawan (UNIVERISTAS PGRI MADIUN, 2022)
We reported the methylene blue (MB) degradation by the photocatalysis method. This work aimed to know the effectiveness of degradation using a MgFe2O4:TiO2 composite. Synthesis of the composite used the sol-gel method. We synthesized three samples with ratios between MgFe2O4 and TiO2. Those were 100:0, 50:50, and 75:25, respectively. Sample (75:25) degraded MB of 47.23% with a reaction rate of 5.326 x 10-3 minute-1 under solar radiation. Whereas, without solar radiation, a sample showed a lower reaction rate. It happened because the sunlight produced photon energy to produce OH* radical so that it could activate the sample to absorb the dye. Reusable test resulted 19.73% degradation of MB for 100:0, 17.03% for 50:50, and 20.59% for 75:25 for 120 minutes. The XRD result for 75:25 has three phases, which are MgFe2O4 with cubic structure, TiO2 with tetragonal structure, and Fe2O3 with hexagonal structure. This work indicated that the sol-gel method could synthesize composite structures, and the sample may be used to remove methylene blue.